MEMBERIKAN BIMBINGAN BELAJAR BAHASA INGGRIS KEPADA ANAK-ANAK NAGARI DUSUN BARU TAPAN DENGAN METODE FUN LEARNING - Suhaimi, Suhaimi; Irawan, Yoki; Hasim, Eliza (Institut Agama Islam Negeri Kerinci, 2021)
English is one of the compulsory subjects that must be taught by every school at all levels, from primary school to university. But sometimes, students find it difficult to understand the material given by the teacher. In addition, the provision of monotonous material may feel boring for students, causing a lack of motivation to learn English. In addition, for elementary students, learning should use teaching methods that involve students. To overcome these problems, Fun English Learning is structured as one of the recommended programs so that teachers can increase the motivation and awareness of elementary students in learning English. Through fun learning methods such as the use of games in learning, students can more quickly absorb material and increase their interest. In addition, students do not get bored when learning English. On the contrary, students feel happy and excited when doing learning activities.The main objective of this program is to provide fun and engaging English language instruction for children so that they can learn with high enthusiasm and enthusiasm. In addition, this program also aims to open their horizons to the culture and diversity of the English language, which will be an important capital in facing future challenges.